Analisis Pengaruh Kinerja Keuangan terhadap Alokasi Belanja Modal di Provinsi Jambi - Eko Indra Praza (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2016)
Abstract.This research aimed to analyze the financial performance of the District/ Municipality in Jambi Province and to determine the effect of financial performance either simultaneously or partially on capital expenditure. The data used in this research is a panel data comprising time series data is data in 2010 - 2013 and cross section data is data of 9 (nine) District and 2 (two) Municipality is located in the Province of Jambi. The analytical method used panel data regression analysis. The analysis showed that the financial performance of the District/ Municipality in Jambi Province is still relatively low as the PAD contribution to regional revenue is still small so transfer income still dominate the local revenue to finance most of the regional expenditure. The results of panel data regression using the Fixed Effect Model (FEM) showed that the financial performance simultaneously significant effect on capital expenditure allocation of the District/Municipality in Jambi Province from 2010 to 2013 and partially Ratio Degree of Decentralization significant positive effect on the allocation of capital expenditure. Financial dependency ratio, Financial Independence Ratio and the ratio degrees contributions public enterprises significant negative effect on capital expenditure . Effectiveness ratio of PAD does not significantly influence the allocation of capital expenditure.Keyword: Financial Performance, Decentralization, Financial Independence,   Abstrak. Penelitian ini bertujuan untuk menganalisis kinerja keuangan Pemerintah Kabupaten/Kota di Provinsi Jambi dan untuk mengetahui pengaruh kinerja keuangan baik secara simultan maupun secara parsial terhadap alokasi belanja modal. Data yang digunakan dalam penelitian ini merupakan data panel yang terdiri dari data time series yaitu data tahun 2010 – tahun 2013 dan data cross section yaitu data 9 (sembilan) Kabupaten dan 2 (dua) Kota yang berada di Provinsi Jambi. Metode analisis yaitu analisis regresi data panel. Hasil analisis menunjukkan bahwa kinerja keuangan Kabupaten/Kota di Provinsi Jambi masih tergolong rendah. Hasil regresi data panel dengan menggunakan metode Fixed Effect Model (FEM) menunjukkan bahwa kinerja keuangan secara simultan berpengaruh signifikan terhadap alokasi belanja modal Kabupaten/Kota di Provinsi Jambi dari tahun 2010 sampai dengan tahun 2013 dan secara parsial  Rasio Derajat Desentralisasi berpengaruh positif signifikan terhadap alokasi belanja modal. Rasio Ketergantungan Keuangan, Rasio Kemandirian Keuangan dan Rasio Derajat Kontribusi BUMD berpengaruh negatif signifikan terhadap alokasi belanja modal. Rasio Efektifitas PAD tidak berpengaruh signifikan terhadap alokasi belanja modal. Kata Kunci : Kinerja Keuangan, Desentralisasi, Ketergantungan Keuangan